Kontestasi Calon Presiden Republik Indonesia 2024 di Media Sosial Hasteg #Prabowo, #AniesBaswedan di Twitter - Ismandianto, Ismandianto; Albintani, Muchid; Suprianti, Najwa; Meliana Putri, Friska (Nakhoda: Jurnal Ilmu Pemerintahan, 2023)
The registration for the 2024 presidential candidates began at the end of 2023, but the euphoria of the 2024 presidential candidates began to be felt since the beginning of 2022. Several survey institutions issued public opinions regarding several 2024 presidential candidates. Public opinion about the 2024 presidential candidates cannot only be obtained through direct interviews. Public opinion acquisition can also be done through social media such as Twitter. Therefore this research has the aim of studying communication networks and determining actors who hold influence in the #Prabowo and #anies baswedan network on Twitter social media. This study uses the Social Network Analysis (SNA) research method or social network analysis with the theory of Computer Mediated Communication. The results of this study show that #Prabowo's information spreads quickly and easily on Twitter. Based on data collected from 2,500 actors, there are a total of 682 interactions between actors in the #Prabowo network. The results of #anies baswedan show that this communication network has a relationship typetwo mode and the network is direct and has the direction of the main actor, namely #anies baswedan with valuedegree centrality 766 and the relationship between actors in this communication network is very close.